Specific to Whose Body? Perspective-Taking and the Spatial Mapping of Valence - Kominsky, Jonathan F.; Casasanto, Daniel (Frontiers in Psychology, 2013)
People tend to associate the abstract concepts of “good” and “bad” with their fluent and disfluent sides of space, as determined by their natural handedness or by experimental manipulation (Casasanto, 2011). Here we investigated influences of spatial perspective taking on the spatialization of “good” and “bad.” In the first experiment, participants indicated where a schematically-drawn cartoon character would locate “good” and “bad” stimuli. Right-handers tended to assign “good” to the right and “bad” to the left side of egocentric space when the character shared their spatial perspective, but when the character was rotated 180 degrees this spatial mapping was reversed: good was assigned to the character’s right side, not the participant’s. The tendency to spatialize valence from the character’s perspective was stronger in the second experiment, when participants were shown a full-featured photograph of the character. In a third experiment, most participants not only spatialized “good” and “bad” from the character’s perspective, they also based their judgments on a salient attribute of the character’s body (a handicapped hand) rather than their own body. Taking another’s spatial perspective encourages people to compute space-valence mappings using an allocentric frame of reference, based on the fluency with which the other person could perform motor actions with their right or left hand. When people reason from their own spatial perspective, their judgments depend, in part, on the specifics of their bodies; when people reason from someone else’s perspective, their judgments may depend on the specifics of the other person’s body, instead.